Germline mosaicism of a missense variant in KCNC2 in a multiplex family with autism and epilepsy characterized by long‐read sequencing. Issue 7 (2nd April 2022) - Mehinovic, Elvisa; Gray, Teddi; Campbell, Meghan; Ekholm, Jenny; Wenger, Aaron; Rowell, William; Grudo, Ari; Grimwood, Jane; Korlach, Jonas; Gurnett, Christina; Constantino, John N.; Turner, Tychele N.
Abstract: Currently, protein‐coding de novo variants and large copy number variants have been identified as important for 30% of individuals with autism. One approach to identify relevant variation in individuals who lack these types of events is by utilizing newer genomic technologies. In this study, highly accurate PacBio HiFi long‐read sequencing was applied to a family with autism, epileptic encephalopathy, cognitive impairment, and mild dysmorphic features (two affected female siblings, unaffected parents, and one unaffected male sibling) with no known clinical variant. From our long‐read sequencing data, a de novo missense variant in the KCNC2 gene (encodes Kv3.2) was identified in both affected children. This variant was phased to the paternal chromosome of origin and is likely a germline mosaic. In silico assessment revealed the variant was not in controls, highly conserved, and predicted damaging. This specific missense variant (Val473Ala) has been shown in both an ortholog and paralog of Kv3.2 to accelerate current decay, shift the voltage dependence of activation, and prevent the channel from entering a long‐lasting open state. Seven additional missense variants have been identified in other individuals with neurodevelopmental disorders ( p = 1.03 × 10 −5 ). KCNC2 is most highly expressed in the brain; in particular, in the thalamus and is enriched in GABAergic neurons. Long‐read sequencing was useful in discovering the relevant variant in this family with autism that had remained a mystery for several years and will potentially have great benefits in the clinic once it is widely available.